The impacts of asset impairments on performance in the Taiwan listed electronics industry - Wang W.-K.; Chan Y.C.; Lu W.-M.; Chang H. (Taylor and Francis Ltd., 2023)
Data envelopment analysis; Managers; Asset impairments; Average efficiencies; Dynamic data; Dynamic performance; Earnings management; Empirical findings; Operating performance; Poor performance; Electronics industry